Prof. Mr. Soediman Kartohadiprodjo tentang Pancasila sebagai pandangan hidup bangsa Indonesia - Kartohadiprodjo, Soediman, 1908-1970.; Kartohadiprodjo, Achmad Suhardi ([Jakarta] : Gatra Pustaka, 2010)
On Pancasila, five principles of Indonesian ideology; collected articles.
Includes bibliographical references (p. 432).
Keywords: Civics, Indonesian; National characteristics, Indonesian; Pancasila; Indonesia -- Politics and government